Positive effects of dietary fiber from sweet potato [Ipomoea batatas (L.) Lam.] peels by different extraction methods on human fecal microbiota in vitro fermentation - Cao, Yan; Tian, Baoming; Zhang, Zhiguo; Yang, Kai; Cai, Ming; Hu, Weiwei; Guo, Yang; Xia, Qile; Wu, Weicheng (Frontiers in Nutrition, 2022)
Abstract The purpose of this study was to compare the effects of sweet potato peels dietary fiber obtained by different extraction methods on intestinal health. Specifically, four different dietary fibers were extracted by hot water, microwave, ultrasonic and subcritical water methods. And the prebiotics effects of sweet potato peels dietary fibers were explored in an in vitro fermentation model, by determining intestinal gas content, short-chain fatty acid content, pH, ammonia content and the gut microbiota composition. The results showed that dietary fiber obtained by four different extraction methods could be utilized by GM and improve human health by increasing the abundance of beneficial bacteria (e.g. Bifidobacterium, Faecalibacterium, and Prevotella) and reducing the abundance of harmful bacteria (e.g. Proteobacteria, Romboutsia and Dorea), enhancing the relative abundance of SCFA-producing bacteria, promoting the production of short-chain fatty acids, reducing intestinal pH from 6.89 to 4.63 and ammonia. Among them, dietary fiber extracted by ultrasound is better than the other three extraction methods. This study suggests that all the four different extraction methods are available for sweet potato peels dietary fiber, and the extracted dietary fiber could be served as potential functional foods with great development value. In addition, it is beneficial to reduce the environmental pollution of sweet potato peels and improve the high-value processing and utilization of sweet potato by-products.